The The Relationship Between Public Expenditures and Economic Growth in the Scope of Economic Classification: The Case of Turkiye - Balkı, Ali; Göksu, Serkan (Panoeconomicus, 2023)
The relationship between public expenditures and economic growth is a constantly debated topic among researchers. There are five main models used to test Wagner's Law. This study aims to test Wagner's Law for Turkiye's public expenditure and expenditure types within the scope of economic classification by using all models in the literature. We tested the validity of Wagner's Law in the Turkiye case using the ARDL method applied for the years 1950–2020. Study findings prove that Wagner's Law is valid in Turkiye using the Mann and Peacock models for public expenditure. In addition, the findings support Wagner's Law only in transfer expenditures among sub-components. These findings point out that public expenditure, which increases more than gross domestic product, is dominated by transfer expenditures. The fact that social transfers account for approximately 75% of transfer expenditures in the last decade demonstrates that Turkiye prioritizes the social state function. JEL: E60, H50, O40, C32.